Pengaruh Kompensasi, Gaya Kepemimpinan Dan Persepsi Dukungan Organisasi Terhadap Turnover Karyawan BMT NU Di Kabupaten Bondowoso - Mohammad Rohib Hasani; Akhmad Suharto; Rusdiyanto (Universitas Muhammadiyah Metro, 2025)
A high employee turnover rate can be a serious challenge for organizations, including BMT NU inBondowoso Regency, because it has an impact on workforce stability, productivity, and increasesrecruitment and training costs. Factors that can influence employee turnover include compensation,leadership style, and perceptions of organizational support. This research aims to analyze theinfluence of compensation, leadership style, and perceptions of organizational support on employeeturnover at BMT NU Bondowoso Regency. This research uses a quantitative approach with a surveymethod by distributing questionnaires to 104 BMT NU employees in various branches in BondowosoRegency. Data analysis was carried out using multiple linear regression to test the influence ofindependent variables on employee turnover. The research results show that compensation andleadership style have a significant influence on employee turnover, where better compensation and aneffective leadership style can reduce turnover rates. In contrast, perceived organizational supportdoes not have a significant influence on employee turnover, although in theory it can increaseemployee loyalty and retention. Based on these findings, organizations are advised to improvecompensation systems that are fairer and more competitive and implement a more participativeleadership style to create a more stable work environment and support employee retention in the longterm.